Between Teaching and Research: Challenges of the Academic Profession in Croatia - Marko Turk (University of Ljubljana, 2016)
Discussions about synergy or independence of teaching and research are present in many studies (Bilić, 2009; Brew & Boud, 1995; Enders & Teichler, 1997; Griffiths, 2004; Jakovljević, 2010; Jenkins, 2000; Ramsden & Moses, 1992). Humboldt’s model introduced synergy between teaching and research, thus highlighting the importance of originality in scientific work and of the dissemination of the knowledge stemming from it. The synergy between teaching and research is also referenced in the education policy of the European Union, with the Berlin Communique (2003) introducing a request for the promotion of better synergy between European educational and research areas. However, studies reveal a different understanding of the teaching-research relationship between those who advocate their synergy (Brew & Boud, 1995; Jenkins, 2000; Neumann, 1993) and those who advocate their mutual independence (Hattie & Marsh, 1996; Ramsden & Moses, 1992). Examining different perspectives of the teaching-research relationship, the research presented in this paper focused on understanding how academics see their dominant roles. Its objective was to examine how academics perceive their roles as teachers and researchers. A qualitative approach was used, with data being collected using a standardised semi-structured interview. A total of 60 interviewees participated in the research, all academics from Croatia. The results revealed that the research participants see themselves most frequently as teachers, then as teachers and researchers, and least frequently as predominantly researchers. Their identification is mainly determined by external factors, most frequently negatively connoted, which presents a challenge within the context of job satisfaction. Such results also point to legal, material, personnel and administrative difficulties in the Croatian higher education system.